In situ atomic level dynamics of heterogeneous nucleation and growth of graphene from inorganic nanoparticle seeds. - Gong, C; He, K; Lee, G; Chen, Q; Robertson, A; Yoon, E; Hong, S; Warner, J (American Chemical Society, 2016)
An in situ heating holder inside an aberration-corrected transmission electron microscope (AC-TEM) was used to investigate the real-time atomic level dynamics associated with heterogeneous nucleation of graphene from Au nanoparticle seeds. Heating monolayer graphene to an elevated temperature of 800o C resulted in the removal of the majority of amorphous carbon adsorbates to leave a clean surface and also the aggregation of Au impurity atoms into nanoparticle clusters that were bound to the monolayer graphene. These Au nanoparticles residing on the surface of monolayer graphene cause inhomogeneous nucleation of secondary graphene layers from carbon feedstock present within the microscope chamber. The growth mechanism is found to consist of alternating processes of C cluster attachment and indentation filling to maintain a uniform growth front of low energy. In several cases we observe small back-folded edge sections of the graphene that can grow in reverse direction before finally flipping over and reattaching to the surrounding region. The secondary layer domains start as highly polycrystalline, but evolve with time into better crystallinity. Tight-binding molecular dynamics (TBMD) simulations are used to understand the detailed lowest energy step-by-step pathways associated with GB migration and crystallization processes. We find the motion of the GB is discontinuous and mediated by both bond rotation and atom evaporation, supported by density functional theory calculations and TBMD. These results provide insights into the formation of crystalline seed domains that are generated during bottomup graphene synthesis.